catena-Poly[[tribenzyltin(IV)]-mu-2-(piperidin-1ylcarbothioylsulfany l)acetato-kappa O-2/O `] - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Sn atom in the title polymeric compound, [Sn(C7H7)(3)-(C8H12NO2S2)](n), exists in a trans-C3O2 trigonal-bipyramidal coordination environment in the two independent formula units. The carboxylate moiety functions in a bridging mode, linking adjacent triorganotin cations into a linear chain running along the shortest axis of the triclinic unit cell; the repeat distance of the polymer is half the a-axial length. In one formula unit, the Sn atom is displaced out of the equatorial plane in the direction of the Sn-O-covalent bond by 0.093 (4) angstrom and in the second molecule, the Sn atom is displaced by 0.105 (4) angstrom in the same direction.